Relationship between diabetic nephropathy and depression: a cross-sectional analysis using the Diabetes Study from the Center of Tokyo Women's Medical University (DIACET) - Takasaki, Keiko (BMJ Open Diabetes Res Care, 2016)
OBJECTIVE: We conducted this cross-sectional study to investigate the relationship between stage of diabetic nephropathy and likelihood or severity of depression in patients with diabetes. RESEARCH DESIGN AND METHODS: We studied 2212 patients with diabetes (mean age 60.9 years; 928 women; 1838 patients with type 2 diabetes). Presence and severity of depression was examined using the Patient Health Questionnaire-9 (PHQ-9). Patients were classified into 5 stages of nephropathy, according to albuminuria and estimated glomerular filtration rate (eGFR); patients in stage 5 undergoing dialysis and kidney transplantation were analyzed separately (stages 5D and 5T). The relationship between stage of nephropathy and depression was examined using analysis of covariance and multivariate logistic regression analysis. RESULTS: Both least square mean PHQ-9 scores and prevalence of patients with PHQ-9 scores ≥5 points (mild depression) and ≥10 points (moderate or severe depression) increased from stage 1 to 5D, and then declined in stage 5T. Multivariate ORs for mild or greater depression increased in patients in stages 3, 4, and 5D in reference to those in stage 1, which declined in patients in stage 5T. Albuminuria was significantly, but eGFR was not, associated with higher PHQ-9 scores and the PHQ-9 scores ≥5 or ≥10 after adjustment for clinical findings. CONCLUSIONS: In patients with diabetes, progression of nephropathy is likely to be associated with increased risk and severity of depression, which may be reduced after successful kidney transplantation. Albuminuria may be more strongly associated with depression than eGFR.